2013
DOI: 10.2478/abcsb-2013-0018
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cadmium-Induced Root Subapical Hair Development and Ethylene Biosynthesis in Oilseed Rape Seedlings

Abstract: It has long been observed that toxic heavy metals at different concentrations can induce root hair development in plants. In oilseed rape we studied ethylene levels and root hair initiation under Cd 2+ stress. Growth of the primary root was inhibited but close to root tips the development of subapical root hairs was significantly stimulated by Cd 2+ at 30 μM. Versus the control, the distance between the root tip and the root hair zone and the length of the epidermal cell in the elongation zone were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…This was attributed to an increased uptake of Pb and a diminished GSH content (Cao et al, 2009 ), revealing crosstalk between ethylene and the biosynthesis of this antioxidant and metal chelating compound. Also other studies link ethylene to the metal-induced oxidative stress response (Sun and Guo, 2013 ; Zhang et al, 2014 ; Montero-Palmero et al, 2014a ; Schellingen et al, 2015a , b ), as is discussed in the next section. These results clearly point toward the potential benefit of altering ethylene biosynthesis and/or signaling in future phytoremediation strategies (Montero-Palmero et al, 2014a ).…”
Section: Ethylene Is a Key Regulator Of Plant Responses To Metal Strementioning
confidence: 92%
See 2 more Smart Citations
“…This was attributed to an increased uptake of Pb and a diminished GSH content (Cao et al, 2009 ), revealing crosstalk between ethylene and the biosynthesis of this antioxidant and metal chelating compound. Also other studies link ethylene to the metal-induced oxidative stress response (Sun and Guo, 2013 ; Zhang et al, 2014 ; Montero-Palmero et al, 2014a ; Schellingen et al, 2015a , b ), as is discussed in the next section. These results clearly point toward the potential benefit of altering ethylene biosynthesis and/or signaling in future phytoremediation strategies (Montero-Palmero et al, 2014a ).…”
Section: Ethylene Is a Key Regulator Of Plant Responses To Metal Strementioning
confidence: 92%
“…Ethylene might therefore modulate lateral root outgrowth during high Cd exposure (Remans et al, 2012 ). Furthermore, ethylene is implicated in the development of root hairs in Cd-exposed B. napus seedlings, as the use of the ethylene biosynthesis inhibitors cobalt chloride (CoCl 2 ) and aminooxyacetic acid (AOA) attenuated the Cd-mediated increase in root hair density (Sun and Guo, 2013 ). Ethylene may also inhibit primary root growth during the early response to Hg, as roots of M. sativa seedlings exposed to the ethylene receptor inhibitor 1-methylcyclopropene (1-MCP) as well as roots of ethylene insensitive ein2-5 A. thaliana mutants grew more in the presence of moderate Hg concentrations as compared to their untreated or WT counterparts (Montero-Palmero et al, 2014a ).…”
Section: Ethylene Is a Key Regulator Of Plant Responses To Metal Strementioning
confidence: 99%
See 1 more Smart Citation
“…The conventional understanding is that root hairs increase root surface area, thereby enhancing metal uptake, which then results in increased toxicity and lower EC50 . It was reported that the root elongation of oilseed rape seedlings was reduced after root hair density increased when there was exposure to toxic levels of Cd 2+ , and similar results were found for signal and Rhodes grass . Therefore, root hairs are important in determining the root elongation response to toxicity.…”
Section: Discussionmentioning
confidence: 81%
“…The negative effects of Cd have been observed through reductions in photosynthesis rate and root elongation, and have been suggested to be a generic stress-induced morphogenic response (SIMR) similar to those detected with other heavy metals or UV-B radiation (Parrotta et al, 2015). A signature of SIMR, e.g., clustered root hairs near the apex, was shown in rapeseed under Cd stress (Sun and Guo, 2013). However, no molecular mechanism has been suggested to explain this phenomenon.…”
Section: Introductionmentioning
confidence: 99%